DAMPAK SOSIAL KONVERSI LAHAN PERTANIAN (STUDI KASUS KELURAHAN KUBU GULAI BANCAH KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI) - Latifa Hayati; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine the factors that affect the farming community agricultural land conversion and social impact of the conversion of agricultural land to the people in the village of Kubu Gulai Bancah District Mandiangin Koto Selayan City Bukittinggi. This study uses quantitative methods were analyzed descriptively. The research location is in the village of Kubu Gulai Bancah District Mandiangin Koto Selayan City Bukittinggi with respondents as many as 27 people and key informant as much as 5 people. The results showed that the factor that many respondents expressed is because they are old and no longer strong enough to farm again. The damage caused to the farmers that they felt their economic life is much more increased. While the impact is felt by the people in the village of Kubu Gulai Bancah District Mandiangin Koto Selayan City Bukittinggi is positive impacts and negative impacts. Positive impact felt by the public that is the improvement of transportation facilities, health facilities, educational facilities and the presence of new jobs for the community. While the negative impact that the crimes that have sprung up as the spread of narcotics in the community, especially in adolescents and deviant behaviors such as promiscuity that led to the pregnant out of wedlock. Keywords: Social Impacts, Land Conversion, Kubu Gulai Bancah Village